THE EFFECTIVENESS OF USING STORY MAPPING TO IMPROVE STUDENTS’ READING COMPREHENSION SKILL IN ENGLISH NARRATIVE TEXT ON X TKJ AT SMK NU PACE - Mohamad Ali Murtadlo; Puput Zuli Ekorini (Universitas PGRI Mpu Sindok, 2025)
Reading comprehension skills are very important in an educational context, especially for students learning English as a foreign language. This study aims to evaluate the effectiveness of the story mapping method in enhancing students' reading comprehension skills in English narrative texts. The research was conducted at SMK NU Pace, focusing on students in class X TKJ-2, consisting of 30 students as a sample from a population of 207 students. The method used was Quasi Experimental with a One Group Pre-test - Post-test design. Data were collected through reading tests administered before and after the implementation of the story mapping method. Data analysis was performed using the sample t-test to determine significant differences in students' reading abilities. The results showed a significant difference in students' reading comprehension skills before and after the application of story mapping, with a t-value obtained of > = 1.699 (at a significance level of 5% and degrees of freedom = 29), indicating that the alternative hypothesis is accepted. So “There is a significant difference before and after being taught by using story mappimg effectively to improve reading comprehension of class X TKJ students at SMK NU Pace in the academic year 2023-2024”.